1997
DOI: 10.1021/jm960626t
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Potent Isoxazoline Glycoprotein IIb/IIIa Receptor Antagonists

Abstract: Using the isoxazoline as a common structural feature, three series of glycoprotein IIb/IIIa receptor antagonists were evaluated, culminating in the discovery of XR299 (30). In an in vitro assay of platelet inhibition, XR299 had an IC50 of 0.24 microM and was a potent antiplatelet agent when dosed intravenously in a canine model. It was shown through X-ray studies of the cinchonidine salt 49 that the receptor required the 5(R)-stereochemistry for high potency. The ethyl ester prodrug of XR299, XR300 (29), was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 34 publications
3
40
1
1
Order By: Relevance
“…(R,S)-(4-Cyanophenyl)isoxazolinylacetic acid (3), the corresponding (R)-and (S)-enantiomers, and the (R,S)-(4-N-Bocamidinophenyl)isoxazolinylacetic acid (4) were synthesized as described previously. 19,20 N 2 -Sulfonyldiaminopropionate Derivatives. Alkyl-, aryl-, and heteroarylsulfonyl chlorides were available from commercial sources or were prepared using literature methods.…”
Section: Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…(R,S)-(4-Cyanophenyl)isoxazolinylacetic acid (3), the corresponding (R)-and (S)-enantiomers, and the (R,S)-(4-N-Bocamidinophenyl)isoxazolinylacetic acid (4) were synthesized as described previously. 19,20 N 2 -Sulfonyldiaminopropionate Derivatives. Alkyl-, aryl-, and heteroarylsulfonyl chlorides were available from commercial sources or were prepared using literature methods.…”
Section: Chemistrymentioning
confidence: 99%
“…[9][10][11][12][13][14][15] Results from clinical trials of GPIIb/IIIa antagonists suggest that substantial inhibition of platelet aggregation may be achieved without unduly compromising hemostasis and that GPIIb/IIIa blockade may lower the risk of thrombotic events in the context of unstable angina and following coronary angioplasty. 16- 18 We recently reported that isoxazolinylacetamides of -alanine are highly effective frameworks for the display of the basic and acidic functionality requisite to high GPIIb/IIIa affinity 19 and that the R-carbamate diaminopropionate 1 (DMP 754) [20][21][22] provides high oral potency and prolonged antiplatelet effects in dogs as compared to the R-unsubstituted analogue 2 (XR300). 19 The use of N-R-substituted diaminopropionates in other series of GPIIb/IIIa antagonists has been recently reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors reported the resolution of (2) by using chinchonidine with 29% yield and 98% ee. [5] Enzymatic hydrolysis of butyl esters with lipase P30 gave 41.5% yield and 98% ee. [4] In our hands, we could not achieve more than 64% ee for resolution after three crystallizations and 42% ee for enzymatic hydrolysis.…”
Section: Resultsmentioning
confidence: 99%
“…We repeated the experiment with the acid 2 (64% ee) and coupling with 1.1 equivalent of amine to get 4b in 79% yield with 90% de. Compound 4b was converted into roxifiban 5a by a reported method [5] to give a chiral purity of 93.2% de.…”
Section: Roxifiban Synthesis 4159mentioning
confidence: 99%